The role of technological intensity, cluster membership, and internationalisation for greater green innovation: The case of the Valencian Community - Valdivieso-Uvidia, Jeanneth Marcela (2025)
This study analyses differences in the development of green innovation among manufacturing firms in the Valencian Community, Spain. Based on factors related to technological intensity, territorial integration and internationalisation, this research assesses whether firms follow different patterns when it comes to engage in product- and process-related green innovation. The findings indicate that the industry's technological intensity is a catalyst for green innovation development, with technologically advanced sectors demonstrating a higher intensity in the adoption of green products and production processes. Moreover, territorial  anchoring, based on industrial cluster membership, enhances green product innovation, while the demands for international markets are positively associated with both green product and process innovation. The findings have important implications for regional economic development, highlighting the need for developing business and institutional specific support strategies for low technology-intensive sectors, strengthening industrial clusters as collaborative ecosystems, and supporting firms'  internationalisation for greater corporate sustainability.